Analysis of Trend and Detection of Change Points in Lake Urmia Level and Climatological Parameters Using R Software - Hanieh Mohammadi; Keivan Khalili; Hossein Rezaie; Amin Amini-Rakan (Water Harvesting Research)
In recent decade, there has been a substantial reduction in the water level of Lake Urmia. Understanding the underlying causes and pivotal moments of these changes, always have importance in environmental and water resources studies. This study aims to analyze the water level fluctuation, the climatic parameters trends and their interrelationship in Lake Urmia Basin. The data were collected from Urmia airport synoptic station and over 50 years, from 1973 to 2022 on a monthly and annual scale. For trend analysis, the Mann-Kendall, seasonal Mann-Kendall, and correlated seasonal Mann-Kendall tests and for change detection, Standard Normal Homogeneity Test (SNHT), Pettitt's test, the Buishand range test, and U Buishand test, were used. The results of study showed that, the maximum and average temperatures time series showing an increasing trend and the minimum relative humidity demonstrating a decreasing trend. Also, a significant decreasing trend was observed in the lake's water level during this period.  Change point tests identified the years 1999 to 2001 as the turning point for the lake's water level, and for other parameters, change points were in the 1990s on both annual and seasonal scales. Furthermore, the lake's water level exhibited different behaviors before and after the change points. The results of this study, indicates a major climate change in the Lake Urmia catchment since year 2000, resulting water level decrease and dry up in this lake.